In situ protein degradability of certain feedstuffs in the rumen of cattle - CHANDRASEKHARAIAH, M; SAMPATH, K T; THULASI, A; ANANDAN, S (The Indian Journal of Animal Sciences, 2014)
In situ crude protein (CP) disappearance of soybean extraction, sunflower extraction, rapeseed extraction, maize gluten meal-60 (60% CP), maize gluten meal-40 (40% CP), copra-cake extraction, safflower-cake, broken rice, jowar grain, ragi grain, rice polish and maize bran in the rumen at different incubation periods were determined by nylon bag technique using 3 adult fistulatedÂ·steers. The residual CPÂ·values were transformed to natilrallogarithms and then subjected to linear regression to arrive at degradation constants. The effective degradability was calculated for an assumed out flow rate of 5%/hr. The effective CP degradability of soybean extraction, sunflower extraction, rapeseed extraction, maize gluten meal-60, maize gluten meal-40, copra-cake extraction, safflower-cake, broken rice, jowar grain, ragi grain, rice polish and maize bran was 54, 54, 69, 21,37,33,63,32,15,32,47 and 37% respectively. Maize gluten meal-60, maize gluten meal40, soybean extraction and copra-cake extractions provided high amounts of UDP (490, 252, 210 and 150g) per kg dry matter as compared to other protein supplements. The energy supplements (ragi grain, jowar grain, broken rice, maize bran and rice polish), although in small quantities, contribute more undegradable protein than rumen degradable protein at an outflow rate of 5%/hr.